(untitled) (Journal of history, 2021)
As you know, in the thirty years since independence, a number of changes have occurred in Russian science. However, drawing lessons from the past, it is known that in order to correctly predict the future, the past of our country begins to be revised from the point of view of new views. One of these topics that require rethinking today is the history of the Soviet period, which is one of the most relevant pages in the history of the Fatherland, including the policy of Russification of the spiritual world of the Kazakh people with the promotion of the educational idea of the Soviet government. With the establishment of Soviet power, there were changes in the language policy. The changes taking place in the Kazakh society, such as the works and exploits of the Kazakh enlighteners, schools related to literacy, the education of the Kazakh youth, the change of letters, are still one of the topics that need to be studied. The article deals with the policy of Russification of the Kazakh society by the Soviet government in the early twentieth century. Russian Russian literature tells about the spiritual colonization of the Kazakh society of that period, the fight against illiteracy, the opening of a large number of Russian schools, the importance of learning the Russian language, and the essence of the policy of reforming letters. Key words: reform, illiteracy, language, education, colonization, independence.